Energy drinks: A review of use and safety for athletes - Duchan, E.; Patel, N. D.; Feucht, C. (The Physician and Sportsmedicine, 2010)
Abstract: Energy drinks have increased in popularity in adolescents and young adults; however, concerns have been raised regarding the ingredients in energy drinks and their potential negative effects on health. Caffeine, the most physiologically active ingredient in energy drinks, is generally considered safe by the US Food and Drug Administration (FDA), although adverse effects can occur at varying amounts. Guarana, which contains caffeine in addition to small amounts of theobromine, theophylline, and tannins, is also recognized as safe by the FDA, although it may lead to caffeine toxicity when combined with caffeine. The amount of ginseng in energy drinks is typically far below the amount used as a dietary supplement, and is generally considered safe. Taurine, an intracellular amino acid, has been reported to have positive inotropic effects; however, this claim is not supported by research. Most energy drinks also contain sugar in an amount that exceeds the maximum recommended daily amount. Young athletes are increasingly using energy drinks because of the ergogenic effects of caffeine and the other ingredients found in these beverages. Energy drinks combined with alcohol are also gaining popularity in young adults, which poses significant concerns about health risks. Other health concerns related to consumption of energy drinks include case reports of seizures and cardiac arrest following energy drink consumption and dental enamel erosion resulting from the acidity of energy drinks.